Preventing the spread of Covid-19 through the habit of proper washing hands for madrasah diniyah students - Fajrin, Fitriana Ikhtiarinawati; Handrianto, Prasetyo; Khusna, Naila Shofa Nida’ul (Community Empowerment, 2021)
Covid-19 has become a global pandemic and affects all ages, including children. This service activity is intended to prevent the spread of Covid-19 for madrasah diniyah students. This service was carried out through health education, both lectures and demonstrations. The results of this activity revealed that the habit of proper hand washing can be instilled through the delivery of information about the importance of hand washing, 6 steps of proper hand washing, and the practice of washing hands in groups and independently.